VERBA PERFORMATIF DALAM TINDAK TUTUR ILOKUSI PADA NOVEL AYAT-AYAT CINTA 2 KARYA HABIBURRAHMAN EL SHIRAZY - Eka Nurtiana; Auzar Auzar; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the Performative Verb in Discourse of Ilokusi on Novel Ayat-Ayat Cinta 2 Karya Habiburrahman El Shirazy. This study also discusses the descriptions of the form and meaning of illocutionary speech in which there is a performative verb found in the novel Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy. The performative verbs found in this study consist of, verbs of opinion, verbs requesting, verb asking, verbal repeating, verbs pleading, verbs enjoining, proposing verbs, verbs expressing, verbs congratulating, verb promised, and thanking verbs. This study uses a qualitative approach and descriptive method that aims to describe the shape and meaning of perfromative verbs in the illocutionary speech contained in the novel Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy. The results of the research are descriptions of the form and meaning of performative verbs in the illokusi speech found in the novel Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy.Keywords: performative verbs, discourse ilocusions, novels of Ayat-Ayat Cinta 2